The Influence of Technology Accepted Model (TAM), Social Influence and Trust on Interest in Using Islamic M-Banking - Navaa, Navaa Tsaltsa Nabila; Ummu, Ummu Salma Al Azizah; Arief, Arief Fitriyanto (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
ABSTRACT This study aims to determine the effect of Technology Accepted Model (TAM), Social Influence and Trust on Interest in Using Sharia M-Banking. The variables studied are